Preoperative prediction of early recurrence of HBV-related hepatocellular carcinoma (≤5 cm) by visceral adipose tissue index - Wu, Zong-qian; Cheng, Jie; Xiao, Xi-xi; Zhang, Hua-rong; Wang, Jian; Peng, Juan; Liu, Chen; Cai, Ping; Li, Xiao-ming (Frontiers in Surgery, 2023)
Background: This study aimed to investigate whether visceral adipose tissue index (VATI) is a significant risk factor for the early recurrence (ER) of HBV-related hepatocellular carcinoma (HCC) (≤ 5 cm) after hepatectomy. Methods: The recruited cohort patients who were positive for hepatitis B virus, presented with surgically confirmed HCC (≤ 5 cm) from Army Medical University (internal training cohort: n=192) and Chongqing Medical University (external validation group: n=46). We measured VATI, subcutaneous adipose tissue index (SATI) via computed tomography (CT). ER was defined as recurrence within 2 years after hepatectomy. The impact of parameters on outcome after hepatectomy for HCC was analyzed. Results: Univariate analysis showed that alpha-fetoprotein levels (p = 0.044), body mass index (BMI) (p < 0.001), SATI (p < 0.001), and VATI (p < 0.001) were significantly different between ER and non-ER groups in internal training cohort. Multivariate analysis identified VATI as an independent risk factor for ER (odds ratio = 1.07, 95% confidence interval: 1.047–1.094, p < 0.001), with a AUC of 0.802, based on the cut-off value of VATI, which was divided into high risk (≥37.45 cm2/m2) and low risk (< 37.45 cm2/m2) groups. The prognosis of low risk group was significantly higher than that of high risk group (p < 0.001). The AUC value of VATI in external validation group was 0.854. Conclusion: VATI was an independent risk factor for the ER, and higher VATI was closely related to poor outcomes after hepatectomy for HBV-related HCC (≤ 5 cm).